2021
DOI: 10.1111/febs.15901
|View full text |Cite
|
Sign up to set email alerts
|

Death domain fold proteins in immune signaling and transcriptional regulation

Abstract: Death Domain Fold (DDF) superfamily comprises of the death domain (DD), death effector domain (DED), caspase activation recruitment domain (CARD) and pyrin domain (PYD). By utilizing a conserved mode of interaction involving six distinct surfaces, a DDF serves as a building block that can densely pack into homo-multimers or filaments. Studies of immune signaling components have revealed that DDF-mediated filament formation plays a central role in mediating signal transduction and amplification. The unique abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 110 publications
0
14
0
Order By: Relevance
“…Evidence is now mounting that LLPS process plays an integral role in the tumorigenesis and progression [ 17 ]. Moreover, the formation of different TIME patterns has also been shown to be correlated with LLPS due to its involvement in the regulation of immune signaling [ 34 , 35 ]. Therefore, we supposed that a comprehensive exploration of LLPS-related biomarkers held great promise for the identification of novel subtypes of tumors, and the prediction of prognosis and immunotherapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is now mounting that LLPS process plays an integral role in the tumorigenesis and progression [ 17 ]. Moreover, the formation of different TIME patterns has also been shown to be correlated with LLPS due to its involvement in the regulation of immune signaling [ 34 , 35 ]. Therefore, we supposed that a comprehensive exploration of LLPS-related biomarkers held great promise for the identification of novel subtypes of tumors, and the prediction of prognosis and immunotherapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…However, the different functions of LLPS in cancer are still unclear. Studies have shown that LLPS could aid in deciphering the heterogeneity of TME ( 34 ), exploring genomic alterations and transcriptional aberrations ( 35 ), and the impact of drug distribution into condensate ( 36 ). LLPS plays multiple roles in carcinogenesis; therefore, identifying LLPS-related biomarkers could offer important insights into defining tumor subtypes and evaluating the prognoses of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mia and Singh [12] discuss how an evolutionary conserved Hippo pathway regulates the proliferation and differentiation of macrophages and epithelial cells in the diverse settings of cardiovascular, pulmonary, liver and gut inflammation, and neuroinflammation. One of the key events in numerous intracellular signalling pathways is the formation of the aggregate‐like macromolecular signalling hub often nucleated by the members of the death domain fold (DDF) superfamily of proteins, extensively reviewed by Huoh and Hur [13]. While for a long time viewed as an inactive misfolded protein depot, it is now clear that the formation of these filamentous macromolecular complexes is essential for the correct concentration and sequestration of effector molecules enabling signal transduction.…”
Section: Figmentioning
confidence: 99%